The Adoption Rite, its Origins, Opening up for Women, and its ‘Craft’ Rituals - Snoek, Jan (REHMLAC+, Revista de Estudios Históricos de la Masonería Latinoamericana y Caribeña plus, 2012)
This essay aims to explain the following questions: When did the Adoption Rite begin? It had its roots in the Harodim tradition in the early 18th century in England. From 1726 onwards there were also lodges of this tradition in Paris. Where did the Adoption Rite come into existence? It was created in France as a modified version of the Rite, used in the Harodim lodges there. Why and under which circumstances was it created? In the 1740s the Harodim lodges were ousted by Moderns lodges. At the same time, French women wanted to be initiated. As a response to both, the Harodim lodges on the continent started to initiate women from 1744 onwards. How did the rituals get their form? The first two degrees of the Rite in use in the Harodim lodges were reworked into the Adoption Rite of three degrees, a Rite of superb quality, and the second of the degrees of the new Rite was designed as a proto-feminist one.